The Synthesis of 3-Nitrooxypropanol, a Methane Mitigant for Sustainable Farming with Environmental Impact: A Review - Marco-Contelles, José (Synthesis, 2023)
Herein it is summarized and critically discussed the different methods reported in the current literature and patents for the synthesis of 3-nitrooxypropanol (3-NOP). Among the small molecules 3-NOP is possibly one of the smallest (chemical formula: C3H7NO4; molecular weight: 121.09) showing interesting biological properties. Particularly, 3-NOP is an efficient inhibitor of methyl CoM reductase, an enzyme that catalyzes the last step of methanogenesis in anaerobic systems (e.g., ruminants), and a potent methane mitigant, able to reduce greenhouse gas emissions and climate change. 3-NOP is the active ingredient of Bovaer, a feed additive for ruminants. Furthermore, 3-NOP has been incorporated in a number of nitrate esters as NO-donors, showing diverse pharmacological activities for the treatment of inflammation or cardiovascular diseases.1 Introduction2 Synthetic Approaches to 3-NOP Based on the Nitrating Agent3 From 3-NOP to Bovaer4 Conclusions
Keywords: Bovaer; methane emission reduction; nitrate esters; nitric acid; 3-nitrooxypropanol; silver nitrate